2011
DOI: 10.1016/j.juro.2010.11.085
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Rhabdosphincter Reconstruction During Robotic Assisted Radical Prostatectomy: Results From a Phase II Randomized Clinical Trial

Abstract: In this randomized clinical trial posterior rhabdosphincter reconstruction offered no advantage for return of early continence after robotic assisted radical prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…Sutherland et al [31] did not find any advantage in the early continence In the present study, we reported a ''tension-free'' anastomosis technique that aimed to restore the anterior and posterior supports to the sphincter. The proposed technique obtained promising outcomes in terms of early continence immediately after catheter removal and at 1 mo, 3 mo, and 6 mo postoperatively.…”
Section: Discussionmentioning
confidence: 49%
“…Sutherland et al [31] did not find any advantage in the early continence In the present study, we reported a ''tension-free'' anastomosis technique that aimed to restore the anterior and posterior supports to the sphincter. The proposed technique obtained promising outcomes in terms of early continence immediately after catheter removal and at 1 mo, 3 mo, and 6 mo postoperatively.…”
Section: Discussionmentioning
confidence: 49%
“…Although Menon et al [27] showed high continence rates for anterior and posterior reconstruction, these authors also found similar results in their control group (single-layer E U R O P E A N U R O L O G Y X X X ( 2 0 1 6 ) X X X -X X X anastomosis). Sutherland et al [28] reported no improvement for posterior reconstruction and interestingly found better results in the control group, even in terms of pad weight (24-h pad test). Our functional reconstruction technique was associated with few complications, and these were similar in both groups.…”
Section: Discussionmentioning
confidence: 97%
“…Joshi [25] Posterior reconstruction did not improve continence after RALP. Sutherland [24] Posterior reconstruction did not increase early return of continence after RALP.…”
Section: Double Layer Anastomosismentioning
confidence: 75%
“…Joshi et al evaluating 94 and 107 patients, respectively [24,25]. Barbed suture has been theorized to simplify and decrease time for the BN anastomosis.…”
Section: Double Layer Anastomosismentioning
confidence: 99%